2016
DOI: 10.17161/bi.v11i0.5860
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Digital Accessible Knowledge of the Plants of Ghana

Abstract: Abstract.-Providing comprehensive, informative, primary, research-grade biodiversity information represents an important focus of biodiversity informatics initiatives. Recent efforts within Ghana have digitized >90% of primary biodiversity data records associated with specimen sheets in Ghanaian herbaria; additional herbarium data are available from other institutions via biodiversity informatics initiatives such as the Global Biodiversity Information Facility. However, data on the plants of Ghana have not as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Biases vary between different data sources and even between different natural history collections [ 6 ]. Records are often more concentrated in more accessible localities, for example near to roads [ 57 ]. In our study we found different relative geographical biases between occurrence record types.…”
Section: Discussionmentioning
confidence: 99%
“…Biases vary between different data sources and even between different natural history collections [ 6 ]. Records are often more concentrated in more accessible localities, for example near to roads [ 57 ]. In our study we found different relative geographical biases between occurrence record types.…”
Section: Discussionmentioning
confidence: 99%
“…A next logical step will be to undertake data gap analyses, to identify discrepancies between current ideas and the state of the entire biodiversity science enterprise in Ghana. An analysis of completeness of digital accessible knowledge exists for the plants of Ghana (Asase and Peterson, 2016), but completeness of digital accessible knowledge for other taxa has not been assessed. This study illustrates how assessing biodiversity data holdings and user data needs can be used to strategize for biodiversity data mobilization, data publication, and data use activities, for a country and/or for a taxon.…”
Section: Discussionmentioning
confidence: 99%
“…Information that is shared and accessible has the potential to impact science and conservation, as well as the care and curation of specimens (Asase and Peterson, 2016). Barriers to sharing biodiversity data could be psychological and behavioral (including legal barriers), or may relate to describing information and data, or may spring from inadequate strategies and resources.…”
Section: Biodiversity Data Mobilization Landscapementioning
confidence: 99%
See 2 more Smart Citations